ANALISIS PENERAPAN SISTEM PENGENDALIAN INTERNAL PADA KUALITAS PELAPORAN KEUANGAN YAYASAN KESEHATAN DAN KESEJAHTERAAN MASYARAKAT DI MAUMERE - Natalia Rosi Permata; Minarni Anachi Dethan (Universitas Nusa Cendana, 2021)
ABSTRACT This study aims to determine and analyze the application of internal control systems based on COSO (Committee of Sponsoring Organizations of the Treadway Commission) theory, including the control enviroment, risk determinations, control activities, communication and information, and supervision have an effect on the quality of financial reporting in the Yayasan Kesehatan dan Kesejahteraan Masyarakat. The type of research is descriptive analysis. The data used are primary data and secondary data. There are four informants in this research. The data analysis technique used is the theory from Milles and Huberman. The results of this study indicate that application of internal control systems in Yakkestra is not fully in accordance with the theory set out in the COSO theory. The financial reporting quality based on ape financial reporting quality standards. Key Word: Internal Contol System, Quality of the financial reporting